Investigations on microstructure and mechanical properties of containing-Si coatings. (3rd July 2017) - Chen, Wanglin; Zhang, Daoda; Yao, Dengcan; Zhang, Shihong; Wu, Weiwei
ABSTRACT: Advanced AlCrSiN and AlTiSiN coatings were deposited on high-speed steel by cathodic vacuum arc. The microstructures, mechanical and tribological properties were studied, as well as cutting performance. The results show that multilayered AlCrSiN coating mainly consists of nanocrystalline fcc-AlCrN and a few amorphous Si3 N4 phases, with an average module period of about 6.0 nm. While the AlTiSiN coating reveals nano-composite structure consisted of nanocrystalline fcc-AlTiN and hcp-AlN embedded into Si3 N4 amorphous matrix. The AlCrSiN-coated tool reveals a more excellent cutting performance when compared with the AlTiSiN-coated tool due to its higher hardness, adhesion strength, H 3 / E * 2 ratio and wear resistance when compared with the AlTiSiN coating.